КОМПЛЕКСНИЙ ПІДХІД ДО ОЦІНКИ КОНКУРЕНТОСПРОМОЖНОСТІ РЕГІОНУ - Chichkan, O.I. (V. Mamutov Institute of Economic and Legal Research of the National Academy of Sciences of Ukraine, 2011)
The paper deals with a theoretical framework for forming the system of region competitiveness indexes, gives grounds for the necessity of estimating competitiveness of the regional system from the point of view of a sustainable development. It offers to divide the factors of regional competitiveness into the undesirable factors of increase of the competitiveness index and factors which condition the increase of the competitiveness on the terms of a sustainable development; the necessity of assessing the influence of each of them on this index is grounded.